Modern parable and utopian thinking by F. J. Hinkelammert - Béjar Bacas, José Serafín (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The present socioeconomic situation is making manifest the crisis of the welfare state. We are running the risk of accepting that neo-liberalism, with the corresponding totalization of the market, is the only possible alternative. Thus, we reach to the fading away of all Utopian thought, accused of unreal, and to giving official approval to a thought that offers itself as the only realistic discourse. In this context, we can also understand the degradation of the politics that, within the given frame, offers itself as mere art of the possible. In order to carry out a critical assessment of the situation, we propose an itinerary through the thought of F. J. Hinkelammert, paying attention to his analysis of the Utopian reason, and to his criticism of neo-liberalism as Utopia or ideology, which hides the actual status quo.